Musical creativities in practice - Burnard, Pamela (Oxford : Oxford University Press, 2012)
This text explores the social and the cultural contexts in which creativity in music occurs. It considers what constitutes creativity, taking a cross cultural view of music, and investigating creative processes far beyond just the classical music genre - including electronic media, popular music, and improvised music.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Composition (Music) -- Psychological aspects; Music -- Social aspects; Creation (Literary, artistic, etc.)